Sexually Transmitted Disease Syndromic Case Management Through Public Sector Facilities: Development and Assessment Study in Punjab Pakistan - Muhammad Amir Khan; Wajiha Javed; Maqsood Ahmed; John Walley; Muhammad Arif Munir (Ubiquity Press, 2015)
Objective: Sexually transmitted infections (STIs) are a priority health problem. We proposed a prospective study in two districts of Punjab, using an intervention package, which included guidelines and protocols on syndrome-based management of STIs, adapted in light of technical guidelines from the National AIDS Control Program and the World Health Organization. The aim of this study was to assess the operational effectiveness of STI case management guidelines and to assess factors that determine the adherence to guidelines for management of STIs at public health facilities in Pakistan. Methods: A prospective study lasting 18 months (January 2008 to June 2009), which reviewed early implementation experiences of updated case management guidelines for delivery of syndrome-based STI/reproductive tract infection care, through public-sector health care facilities. The project was implemented in two districts of Punjab, Sargodha and Jhang. A Cox regression model with stratification was done. Findings: The prevalence of STI was 26 per 100,000 patients. In women, the reported symptoms were 80% vaginal discharge and 12% abdominal pain. Forty-four percent of men had a genital ulcer and 29% of men had genital discharge. Age of participants ranged from 13 to 60 years. The study comprised 28.6% men and 71.4% women. The majority of the population attending these clinics was from rural areas (70%). The variables independently associated with adherence to guidelines were availability of male paramedic, age of patient, and type of diagnosis made. There was an important interaction (effect modification) present between the area of health facility and patient sex. Conclusion: Screening, diagnosis, and treatment costs for many STIs are expensive and thus an easier, low-cost, syndrome-based public health strategy is the adoption of the proposed STI syndrome case management guidelines.